Análisis de los factores de la evasión tributaria y su incidencia en la recaudación. - Molina Velez, Yuri Gabriela (2018)
The present work is presented as a very important subject which is in force the same one that every day charges interest in Ecuador, since the tax evasion is an illicit which influences the collection thus damaging the state, for an interview was used to the personnel of Industria Cartonera Palmar, questions were asked which were linked to the tax evasion variable, by means of these answers the problem could be solved. The tax evasion is presented as a fact of great concern in all countries of the world, due to the effects that come to produce among these the decline in income that has the state, as well as the decrease in private investment, through a bibliographic study could be known as countries get to lose millions of dollars due to tax evasion, for this measures must be taken so that this can be completed and for this evasion should be measured so that in this way the tax administration can improve the tax control. In Ecuador this issue reached a large percentage, a good tactic for this to get better is that taxpayers will come to realize how the state pays the citizenship with the payment of these taxes through public works, services to society , another important point that should be noted is the point where the taxpayer is located since tax evasion starts from here. The tax evasion is produced by the overvaluation of purchases and sales, these errors are given by the breach in terms of the billing regime, for this the tax administration in this case the IRS must have control programs, the same ones that will allow crossing the information, they will have to carry out inspections of omissions, as well as different payments, by means of the tax evasion it will be possible to observe that in the country one arrives to apply an integral model where the incomes are added, that is the income of the taxpayers for their work as well as the capital of a tax base which is unique and that is taxed according to the structure of the marginal rates that are progressive. Due to the effort made by the Ecuadorian tax administration to increase tax collection, it still presents one of the tax pressures which are low in Latin America and the same one that is below the potential. It must be taken into account that the imposition of taxes comes from a principle which has always generated resistance, this occurs in a special way in the classes that are more affluent of all countries, this is where the word appears the one who has more, the more he pays. In Ecuador, according to reports from the SRI in 2016, it is noted that tax evasion still reaches 45%, during the last eight years a new tax approach has been consolidated in Ecuador through regulations, where they were collected in the first semester of 2016 more than $ 10 million in fines due to tax evasion